The Pain of Staying Alert: A Case Report and Literature Review on Energy Drink-Induced Acute Pancreatitis - Navkiran Randhawa DO; Misha Shah BS; Tilemahos Spyratos DO (SAGE Publishing, 2022)
Energy drink consumption has increased over the past decade. It is associated with several common side effects including diarrhea, heartburn, and dyspepsia. Energy drinks have been proposed as a rare but potential cause of acute pancreatitis. This paper investigates a unique case of energy drink-induced pancreatitis and further explores current literature on this topic. This study stresses the importance of asking all patients presenting with acute pancreatitis about their daily energy drink consumption, especially if the cause is unknown.